2022
DOI: 10.1186/s13014-022-02020-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimal management of recurrent and metastatic upper tract urothelial carcinoma: Implications of intensity modulated radiation therapy

Abstract: Background Upper tract urothelial carcinoma (UTUC) is rare and the treatment for recurrent or metastatic UTUC is unclear. We evaluated the outcomes of salvage and palliative radiotherapy (RT) and prognostic factors in UTUC patients and find implications for salvage and palliative RT. Methods Between August 2006 and February 2021, 174 patients (median age, 68 years; range, 37–90) underwent salvage and palliative RT. Disease status at RT included ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The role of radiotherapy (RT) for UTUC management has not been clearly elucidated, since evidence on salvage/palliative RT in patients with recurrent UTUC is still scarce. 73…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of radiotherapy (RT) for UTUC management has not been clearly elucidated, since evidence on salvage/palliative RT in patients with recurrent UTUC is still scarce. 73…”
Section: Resultsmentioning
confidence: 99%
“…The role of radiotherapy (RT) for UTUC management has not been clearly elucidated, since evidence on salvage/palliative RT in patients with recurrent UTUC is still scarce. 73 RT may offer a safe therapeutic alternative in such patients with nonmetastatic UTUC who cannot tolerate or refuse surgery. 74 Therapeutic Approaches: Advanced Disease Role of CT in Metastatic Disease.…”
Section: Clinical Managementmentioning
confidence: 99%
“…In contrast to the EAU guideline, the AUA guideline recommended radiotherapy only as one of the palliative treatment modalities for symptomatic relief in inoperable UTUC patients ( 5 ). A large retrospective study of salvage or palliative radiotherapy in recurrent or metastatic UTUC showed that the treatment is feasible and effective especially with intensity-modulated radiotherapy (IMRT) to escalate higher dose or concurrent chemotherapy to improve the radiotherapy response ( 11 ). In a small case series, five-fraction stereotactic body radiotherapy with dose varied from 35 to 45 Gy is an effective treatment for palliation of gross hematuria from UTUC at the renal pelvis in patients who were unfavorable surgical candidates but have a moderate decline of renal function without patients who required hemodialysis ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Leaving the bladder cuff intact at the time of radical surgery is associated with a known recurrence rate 33–75% in the ureteric remnant ( 62 , 63 ). In 2015, the first series of cases involving pure RAL-NU and BCE was described, demonstrating satisfactory oncologic control at 12months of follow-up ( 64 ).…”
Section: Ral-nu: the Presentmentioning
confidence: 99%